2016
DOI: 10.1186/s40659-016-0083-6
|View full text |Cite
|
Sign up to set email alerts
|

MnSOD and GPx1 polymorphism relationship with coronary heart disease risk and severity

Abstract: BackgroundDisturbance of the equilibrium between reactive oxygen species (ROS) and anti-oxidants (AOX) has been implicated in various diseases, including atherosclerosis, the most common pathologic process underlying coronary heart disease (CHD). Thus, the defense systems against ROS are critical protecting blood vessel walls against oxidative damage. In this study, we investigate whether Ala16Val MnSOD and Pro198Leu GPx polymorphisms are associated with CHD susceptibility and/or severity.MethodsBoth polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 81 publications
(78 reference statements)
4
20
2
1
Order By: Relevance
“…They found that MnSOD Val/Val carriers were associated with higher carotid intimal media thickness, which indicates more severe atherosclerosis [28]. Souiden et al discovered an approximately twofold risk of CAD in Tunisian men harbouring the Val/Val genotype [22]. These results are inconsistent with our data.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…They found that MnSOD Val/Val carriers were associated with higher carotid intimal media thickness, which indicates more severe atherosclerosis [28]. Souiden et al discovered an approximately twofold risk of CAD in Tunisian men harbouring the Val/Val genotype [22]. These results are inconsistent with our data.…”
Section: Discussioncontrasting
confidence: 97%
“…This inconsistency may be due to the influence of interracial MnSOD Ala allele frequency difference. The higher frequency of Ala allele was found as 48.3% in Caucasians and 25.1% in Arabs, respectively [22,28]. It was a discrepancy compared to our Chinese population which was 7.83%.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…It has been shown that the MnSOD Ala 16 Val polymorphism is associated with diabetic nephropathy in patients with type-2 diabetes, 39 diabetic nephropathy in patients with type 1 diabetes, 40 periodontitis disease, 41 and coronary heart disease. 32 There are growing numbers of publications on the −262C/T polymorphism of the catalase gene (rs1001179) in different populations and diseases; although there are GelRed on 2% agarose gel electrophoresis. Lane 1 and 2 shows homozygote "CC" genotype for the one person, Lane 3 and 4 shows heterozygote "CT" genotype for the second person, Lane 5 and 6 shows homozygote "TT" genotype for the third person C and Lane 7 Shows 50 bp DNA molecular markers no reports related to this polymorphism and PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to point out that the V allele also causes SA-HP imbalance, in particular, VV-SOD2 genotypes have been associated with the risk of some metabolic disorders, such as hypercholesterolemia, obesity, and cardiovascular diseases [32][33][34][35][36] and with type 2 diabetes mellitus complications. 37 The explanation for the increase in the susceptibility to these disorders in the VV genotype is that VV genotype cells maintain high basal SA levels that quickly react with nitric oxide (NO) producing extensive alterations in the cells because lipoperoxidation-derived protein carbonylation generates other ROS types.…”
Section: Discussionmentioning
confidence: 99%